The Role of Neutrophil Extracellular Traps in Periodontitis - Wang, Jingyi; Zhou, Yucong; Ren, Biao; Zou, Ling; He, Bing; Li, Mingyun (Frontiers in Cellular and Infection Microbiology, 2021)
Periodontitis is a chronic, destructive disease of periodontal tissues caused by multifaceted, dynamic interactions. Periodontal bacteria and host immunity jointly contribute to the pathological processes of the disease. The dysbiotic microbial communities elicit an excessive immune response, mainly by polymorphonuclear neutrophils (PMNs). As one of the main mechanisms of PMN immune response in the oral cavity, neutrophil extracellular traps (NETs) play a crucial role in the initiation and progression of late-onset periodontitis. NETs are generated and released by neutrophils stimulated by various irritants, such as pathogens, host-derived mediators, and drugs. Chromatin and proteins are the main components of NETs. Depending on the characteristics of the processes, three main pathways of NET formation have been described. NETs can trap and kill pathogens by increased expression of antibacterial components and identifying and trapping bacteria to restrict their spread. Moreover, NETs can promote and reduce inflammation, inflicting injuries on the tissues during the pro-inflammation process. During their long-term encounter with NETs, periodontal bacteria have developed various mechanisms, including breaking down DNA of NETs, degrading antibacterial proteins, and impacting NET levels in the pocket environment to resist the antibacterial function of NETs. In addition, periodontal pathogens can secrete pro-inflammatory factors to perpetuate the inflammatory environment and a friendly growth environment, which are responsible for the progressive tissue damage. By learning the strategies of pathogens, regulating the periodontal concentration of NETs becomes possible. Some practical ways to treat late-onset periodontitis are reducing the concentration of NETs, administering anti-inflammatory therapy, and prescribing broad-spectrum and specific antibacterial agents. This review mainly focuses on the mechanism of NETs, pathogenesis of periodontitis, and potential therapeutic approaches based on interactions between NETs and periodontal pathogens.